Leishmanicidal Potential of Hardwickiic Acid Isolated From Croton sylvaticus - Crentsil, Justice Afrifa; Yamthe, Lauve Rachel Tchokouaha; Anibea, Barbara Zenabu; Broni, Emmanuel; Kwofie, Samuel Kojo; Tetteh, John Kweku Amissah; Osei-Safo, Dorcas (Frontiers in Pharmacology, 2020)
Leishmania is a parasitic protozoon responsible for the neglected tropical disease Leishmaniasis. Approximately, 350 million people are susceptible and close to 70,000 death cases globally are reported annually. The lack of effective leishmanicides, the emergence of drug resistance and toxicity concerns necessitate the pursuit for effective antileishmanial drugs. Natural compounds serve as reservoirs for discovering new drugs due to their chemical diversity. Hardwickiic acid (HA) isolated from the stembark of Croton sylvaticus was evaluated for its leishmanicidal potential against Leishmania donovani and L. major promastigotes. The susceptibility of the promastigotes to HA was determined using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide/phenazine methosulfate colorimetric assay with Amphotericin B serving as positive control. HA showed a significant antileishmanial activity on L. donovani promastigotes with an IC50 value of 31.57± 0.06 µM with respect to the control drug, amphotericin B with IC50 of 3.35 ± 0.14 µM). The cytotoxic activity was observed to be CC50 = 247.83 ± 6.32 µM against 29.99 ± 2.82 µM for curcumin, the control, resulting in a selectivity index of SI = 7.85. Molecular modeling, docking and dynamics simulations of selected drug targets corroborated the observed antileishmanial activity of HA. Novel insights into the mechanisms of binding were obtained for trypanothione reductase (TR), pteridine reductase 1 (PTR1), and glutamate cysteine ligase (GCL). The binding affinity of HA to the drug targets LmGCL, LmPTR1, LdTR, LmTR, LdGCL, and LdPTR1 were obtained as -8.0, -7.8, -7.6, -7.5, -7.4 and -7.1 kcal/mol, respectively. The role of Lys16, Ser111, and Arg17 as critical residues required for binding to LdPTR1 was reinforced. HA was predicted as a Caspase-3 stimulant and Caspase-8 stimulant, implying a possible role in apoptosis, which was shown experimentally that HA induced parasite death by loss of membrane integrity. HA was also predicted as antileishmanial molecule corroborating the experimental activity. Therefore, HA is a promising antileishmanial molecule worthy of further development as a biotherapeutic agent.